Pelaksanaan Pembelajaran Vokal Group Dalam Mata Pelajaran Seni Budaya Di Kelas VII-4 SMP Negeri 3 Padang - Vivi Angraini; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2020)
This study aims to describe implementation of group vocal learning in cultural arts subject at Class VII-4 in SMP Negeri 3 Padang.. Type of this research was a descriptive study with using qualitative method. The research instrument was the researcher. It was assisted by using supporting instruments such as stationery, camera, and voice recorder. Techniques of data collection were carried out by taking observation, interviews, documentation and literature study. The steps in analyzing data were done by collecting, identifying, classifying, clarifying, describing and summarizing data. The results show that group vocal learning carry out by the teacher at class VII-4 in SMP Negeri 3 Padang is not going well and does not catch the target of learning objectives. It can be seen from the planning, implementation, and evaluation that is less relevant between the lesson plans and those implemented by the teacher. The teacher does not understand the concepts and techniques of group vocal singing well so that the students do not understand singing in the form of group vocals. At the time of learning, the teacher should provide musical training to students, so that students' understanding of singing group vocal can be carried out properly, and not just memorizing the song. Therefore, there are still some students who have not been able to practice it properly, due to lack of guided practice, lack of understanding of the material and practice of singing vocal groups correctly which impact on the student grades. In the results of the evaluation of learning to sing in vocal groups of the students at class VII-4, the highest score only reach 87 and the lowest score is 75.